2009
DOI: 10.1073/pnas.0903939106
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylation mechanism and stereochemistry of crotonyl-CoA carboxylase/reductase, a carboxylating enoyl-thioester reductase

Abstract: Chemo-and stereoselective reductions are important reactions in chemistry and biology, and reductases from biological sources are increasingly applied in organic synthesis. In contrast, carboxylases are used only sporadically. We recently described crotonyl-CoA carboxylase/reductase, which catalyzes the reduction of (E)-crotonyl-CoA to butyryl-CoA but also the reductive carboxylation of (E)-crotonyl-CoA to ethylmalonyl-CoA. In this study, the complete stereochemical course of both reactions was investigated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
139
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 55 publications
2
139
0
4
Order By: Relevance
“…In addition, these MOG pathways involve only oxygen‐tolerant enzymes and have predicted lower ATP costs than the Calvin cycle. In addition, synthetic pathways based on crotonyl‐CoA carboxylases, the fastest known carboxylases, may be highly promising to apply in synthetic CO 2 fixation pathways (Erb et al ., 2009). …”
mentioning
confidence: 99%
“…In addition, these MOG pathways involve only oxygen‐tolerant enzymes and have predicted lower ATP costs than the Calvin cycle. In addition, synthetic pathways based on crotonyl‐CoA carboxylases, the fastest known carboxylases, may be highly promising to apply in synthetic CO 2 fixation pathways (Erb et al ., 2009). …”
mentioning
confidence: 99%
“…Recently, it has been shown that they also participate in the fixation of carbon dioxide in alternative carbon fixation cycles [1,23,24,25]. In this cycle one of the important step is the reduction of the α, β -unsaturated thioester by the reduced form of nicotinamide adenosine dinucleotide phosphate (NADPH) to produce an enolate that binds CO 2 (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this cycle one of the important step is the reduction of the α, β -unsaturated thioester by the reduced form of nicotinamide adenosine dinucleotide phosphate (NADPH) to produce an enolate that binds CO 2 (see Figure 1). This reaction is catalyzed by Crotonyl -CoA -carboxylase yielding enantiomeric products and has been widely studied by Erb et al [1]. Recently, enzymes of the same family were shown to also catalyze various thioesters with different substitutions of the alkyl chain [26].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations